2012
DOI: 10.1007/s00339-011-6730-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ambient gas and its pressure on the laser-induced breakdown spectroscopy and the surface morphology of laser-ablated Cd

Abstract: The ablation of Cd has been performed by employing Q-switched Nd: YAG 10 ns laser pulses with a central wavelength of 1064 nm for a pulsed energy of 200 mJ under various ambient environments of argon, air and helium. The optical emission spectroscopy of Cd plasma has been studied under different filling pressures of shield gases ranging from 5 torr to 760 torr using LIBS spectrometer system. The effect of different gases and their pressures on the intensity of spectral emission, electron temperature and densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(38 citation statements)
references
References 16 publications
0
37
1
Order By: Relevance
“…This contrasts with the results reported by Iida, 5 Asimellis et al, 15 and Knight et al 16 and N. Farid et al, 22 who observed a maximum excitation at some finite pressure. The authors attribute such a trend to the interaction of the plasma with the ambient gas where the later acts as an energy buffer transferring a fraction of its energy to the Al plasma in low pressure while at high pressure, collision of electrons with gas atoms increases so that the cascade condition is not favoured and the electron density consequently decreases.…”
Section: Dependence Of Excitation Temperature On Time Delay After contrasting
confidence: 56%
See 1 more Smart Citation
“…This contrasts with the results reported by Iida, 5 Asimellis et al, 15 and Knight et al 16 and N. Farid et al, 22 who observed a maximum excitation at some finite pressure. The authors attribute such a trend to the interaction of the plasma with the ambient gas where the later acts as an energy buffer transferring a fraction of its energy to the Al plasma in low pressure while at high pressure, collision of electrons with gas atoms increases so that the cascade condition is not favoured and the electron density consequently decreases.…”
Section: Dependence Of Excitation Temperature On Time Delay After contrasting
confidence: 56%
“…They attribute these results to the interaction between plasma plume and ambient gas. 5,[16][17][18] It can therefore be concluded from these various observations that there is no clear consensus on the dependence of ablation plasmas on their environment. In this context, the primary objective of the present work is to conduct a deep study of the interplay between the ablated plasma plume and the ambient gas by analyzing the temporal evolution of an Al-plasma in terms of spectral intensity, electron density and excitation temperature within various environments extending from vacuum to atmosphere, and using inert gas like Ar and He as well as chemically active gas like N 2 .…”
Section: Introductionmentioning
confidence: 99%
“…They found that n e and T are maximum at a gas pressure of about 100 Torr. However, another study performed by Bashir et al 16 report a continuous decrease of both n e and T when the ambient gas pressure increases from 5 to 760 Torr during the ablation of cadmium. In our published work, 17 we have shown that, in our conditions, n e and T decrease continuously with the ambient gas pressure ranging from vacuum to atmosphere.…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, based on the McWhirter criterion, the higher values of the electron density measured (see hereafter) in our plasma pushes us to assume that our plasma is in local thermodynamic equilibrium (LTE). Under this assumption, the population of excited states follows the Boltzmann distribution which is given by the following relation 15,16,27 :…”
Section: B Data Processing Methodsmentioning
confidence: 99%
See 1 more Smart Citation